Medicine and public health in twentieth-century China: Histories of modernization and change - Baum, Emily (History compass, 2020)
Over the past two decades, an increasing amount of scholarly attention has turned to the history of medicine in twentieth-century China, with many works demonstrating how the Chinese pursuit of health has been inextricably tied to the quest for national sovereignty and political self-strengthening. This essay examines recent English- and Chinese-language research on the history of medicine, public health, and the body in modern China, focusing specifically on the themes of modernization and change. Proceeding chronologically and thematically, it shows how current historiography has traced the source of China's medical modernization efforts to colonialism, ideological conflicts between practitioners of Chinese and Western medicine, the politicization of medical practice under the Nationalist Party (Guomindang), and the Chinese Communist Party's desire to revolutionize health care.